Studies in the German Drama A Festschrift in Honor of Walter Silz - Crosby, Donald H.; Schoolfield, George C. (UNC Studies in the Germanic Languages and Literatures, 1974)
Sixteen of his former colleagues and students join in this volume in honoring Walter Silz. Concentrating on a single theme-the German drama-this volume contains essays and interpretations of plays ranging from Hrotsvit von Gandersheim to Bertolt Brecht. Eight of the sixteen essays deal with dramas from the area of Silz's main concentration-the nineteenth century. Also included are a tribute to Silz and a bibliography of his writings.